The Military in Nation-Building: A Case Study of the USA Intervention in Afghanistan - Aka-Ajani, Awashima; Vande, Philip T. (Kashere Journal of Politics and International Relations, 2025)
The Nation-building efforts in Afghanistan by the United States’ military began with the introduction of combat forces, which were initiated on 7 October 2001, to remove the Taliban regime and eliminate the al-Qaida terrorist network in Afghanistan. This study examined the US military interventions in Afghanistan from 2001 to 2021. The study adopted a secondary methodology and utilized the realist theory as a framework of analysis. It was realized that nation-building takes a long time and its success appears to be linked to maintaining a standing United States military presence in the country. Again, nation-building is more successful if the state has had experience in self-government and if it has had a viable economy. The study also submitted that the military nation-building had a detrimental effect on the moral reputation of the US, as a result of questionable tactics used during military intervention. Again, the long-term military operations in Afghanistan and their failure to achieve set objectives have reduced the US’s appetite for military intervention. The study recommended that, the military should design support troop structure to expand the capacity to perform nation-building operations in post-conflict regions. Again, the military must recognize the significance of building capacity to establish good governance, and it must push down to local commanders, greater authority for contracting and distribution of resources. Lastly, there is need to establish a structure and means for routine coordination with other government agencies and expand civil-military collaboration efforts to include international governmental organisations and non-governmental organisations.